A REVIEW ON ANTI – PYRETIC HERBS IN SIDDHA MEDICINE - Parvathy, Padmini; Venkatachalam, Sreenivasan; Ramamurthy, Murugan; Elansekaran, *Selladurai; Christian, Gnanaraj Johnson (International Journal of Ayurveda and Pharma Research, 2019)
Fever (also known as pyrexia or a febrile response) is defined as a body temperature above the normal range due to an increase in the temperature regulatory set-point. In Siddha medicine fever is considered as a disease which is caused by body heat. According to Sage Theraiyar, the primary cause for fever is ‘Aamam’ or ‘Seetham’ which means an upset in the normal gastrointestinal function could be because of dysbiosis, indigestion, dyspepsia etc. Nowadays fever is emerged as an important indicator for infectious disease and a resource for research. In Siddha system of medicine, there are many herbal drugs that are used as antipyretic ingredients in many formulations. Siddha medicine has a wealth of remedies for the treatment of fever and associated conditions. Among them, herbs like Andrographis paniculata, Cedrus deodara have antimalarial activity. Polyherbal decoction Nilavembu kudineer is administered for Chikungunya, swine flu and dengue. Here an attempt has been made to explore the concepts of fever and some common varieties of herbal medicines used for the treatment of fever in Siddha. This article reviews the anti pyretic activity of the commonly used herbs in Siddha medicine.